Pengaruh E-Wallet Terhadap Manajemen Keuangan Masyarakat: Saving atau Hedonisme - Ramadhani, Aliya; Puspitasari, Dwi; Salsabilla, Firyal; Haq, Permata Nurul; Putri, Silmi Mardyanti; Rozak, Rama Wijaya Abdul; Mulyani, Heni (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
E-wallet has a concept in the form of digital storage of money on an integrated system connected to the internet. The use of e-mail has a big influence on saving attitudes and hedonistic attitudes. This study aims to prove scientifically that using an e-wallet influences financial management, corresponding with activity and hedonistic behavior. The respondents in this study were people of various ages who used e-wall. The total number of respondents is 274. Data collection uses descriptive methods through a quantitative approach. The existing data is managed using a statistical application tool, namely SPSS 25. The results showed that E-Walt had an influence on hedonistic behavior but not on the attitude toward saving.